Recent changes in sediment accumulation rates in Adventfjorden, Svalbard - Ryszard Bojanowski; Witold Szczuciński; Marek Zajączkowski (Oceanologia, 2004)
Recent sediment accumulation rates in Adventfjorden (Svalbard), a small subpolar fjord, were determined by 210Pb and 137Cs dating. Modern rates in the central basin decrease downfjord from 1.87 to 0.87 cm y-1 (2.6 to 1.19 g cm-2 y-1). Comparison of the modern values (1986-2001) with older ones (1963-86) reveals a marked increase in sediment accumulation rates in the last ten years. This correlates well with recent climate changes (warming and increase in precipitation). Comparison with particulate matter flux data indicates that a portion of the sediment is passed on to Isfjorden.